2017
DOI: 10.1007/s00595-017-1503-0
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and risk factors associated with surgical site infection after different types of hepatobiliary and pancreatic surgery

Abstract: The incidence of and factors associated with SSI after the three types of HBPS analyzed differed significantly. To accurately compare hospital performance in relation to SSI following HBPS, the operative procedure category in the surveillance system must be divided into three types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
46
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 20 publications
4
46
0
1
Order By: Relevance
“…The implementation of such a policy in our practice led to a reduction in the incidence of SSI from 26.4% to 14.8%, and when only patients' adherent to the policy were assessed the rate was only 10.7%. This rate of SSI is less than reported in the NSQIP data (H. Pitt, personal communication, March 18, 2018) and the current surgical literature [4,5] and indicates that intelligent antibiotic prophylaxis targeting bacteria likely to be encountered during PD is critical in preventing SSIs in this cohort.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…The implementation of such a policy in our practice led to a reduction in the incidence of SSI from 26.4% to 14.8%, and when only patients' adherent to the policy were assessed the rate was only 10.7%. This rate of SSI is less than reported in the NSQIP data (H. Pitt, personal communication, March 18, 2018) and the current surgical literature [4,5] and indicates that intelligent antibiotic prophylaxis targeting bacteria likely to be encountered during PD is critical in preventing SSIs in this cohort.…”
Section: Discussionmentioning
confidence: 60%
“…In the NSQIP database, surgical site infections (SSIs) were the most common cause of morbidity, accounting for 21% of the postoperative complications with two-thirds being organ/space and one-third superficial SSIs (H. Pitt, personal communication, March 18, 2018). Such high rates for SSI are also reported in the recent literature: 17%-28% for PD [4,5] and so it is certain that this is a genuine problem.…”
mentioning
confidence: 53%
See 1 more Smart Citation
“…This finding is not novel. 16 Although there is no consensus regarding why male patients are predisposed to SSI, studies have shown that, in laparoscopic cholecystectomy, male sex is a predictor of longer and more difficult operations and has a higher rate of conversion. [17][18][19] In addition, it is known that there are sex differences in skin colonization that may be associated with differences in skin thickness, sebum production and skin pH.…”
Section: Discussionmentioning
confidence: 99%
“…Infectious complications are one of the main causes of death. Surgical-site infection rates after HBPS were reported to be about 9.9-23% [8]. Postoperative infectious complication rates for liver resection were reported as 15.6-34% [9][10][11], which adversely affect oncologic outcomes for hepatocellular carcinoma patients [11], potentially resulting in hepatic failure and death.…”
Section: Introductionmentioning
confidence: 99%